WHAT NEW IS BROUGHT BY THE AMENDMENTS TO THE LAW ON THE HIGH JUDICIAL AND PROSECUTORIAL COUNCIL OF BOSNIA AND HERZEGOVINA? - Milinković, Igor M (Glasnik Advokatske komore Vojvodine, 2024)
Independence of the judiciary is one of the key preconditions of the Rule of Law. However, fostering the “culture“ of judicial independence has to be accompanied by constant efforts to develop the mechanisms and “culture“ of judicial accountability and integrity. This need is particularly highlighted in post-authoritarian societies where the independence of the judiciary rests on the unstable foundations of an authoritarian past characterized by the systematic undermining of judicial independence.In recent decades, the means for strengthening judicial independence has been recognized in establishing judicial councils. Judicial councils, independent bodies whose majority of members come from the judiciary, have been “designed to insulate the functions of appointment, promotion and discipline of judges from the partisan political process while ensuring some level of accountability“ (Garoupa, Ginsberg). In recent years, however, an increasing number of authors have begun to acknowledge that the establishment of judicial councils may lead to the emergence of new channels of politicization of the judiciary, which brings to the fore the issue of the accountability of the aforementioned bodies.The paper analyzes provisions of the Law on Amendments to the Law on the High Judicial and Prosecutorial Council of Bosnia and Herzegovina (HJSC BiH), adopted in 2023, which regulate the disciplinary responsibility of judges and the Council members, as well as the procedure of dismissal of the members of the HJSC BiH. The paper will also analyze other provisions of this law, which aim to suppress corruption in the judiciary and strengthen the integrity of the judicial officeholders.
Keywords: judiciary, judicial independence, judicial accountability, judicial self-government, judicial councils, Bosnia and Herzegovina, High Judicial and Prosecutorial Council, corruption, reports on assets and interests